Determination of certain substances in electrotechnical products. Screening. Polybrominated biphenyls, polybrominated diphenyl ethers and phthalates in polymers by gas chromatography-mass spectrometry using a pyrolyser/thermal desorption accessory (Py/TD-GC-MS) Part 3-3, (29th November 2021) - British Standards Institution,
No abstract available